Analisis Isi Pesan Dakwah Habib Husein Ja’far Al-Hadar di Tik Tok @huseinjafar - Sri Mayangsari; Ahmad Fakhruddin Fajrul Islam (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
The development of digital technology has brought a significant transformation in the method of delivering Islamic preaching, one of which is through TikTok social media. Habib Husein Ja'far Al-Hadar emerged as one of the young preachers who utilized this platform effectively with a unique and contextual approach. This study aims to analyze the content of the da'wah message delivered by Habib Husein Ja'far through the TikTok account @huseinjafar. This research focuses on two main problem formulations, namely how the content of the da'wah messages delivered and how the analysis of these messages in the context of da'wah communication. Through the qualitative content analysis method, it was found that Habib Husein Ja'far packaged his da'wah messages with a light approach, relevant to current trends, and used a communicative and inclusive language style. The messages contain moral, spiritual, and social values that are delivered in a brief but impactful manner, so as to attract attention and build closeness with the audience, especially the younger generation. The findings show that a social media-based da'wah strategy with an adaptive and communicative approach can increase the effectiveness of spreading Islamic values in a digital society.